2015
DOI: 10.1097/hnp.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Management Among Dentists

Abstract: Musculoskeletal disorders (MSDs) are one of the most important occupational health issues in health care workers. Musculoskeletal pain is an occupational health problem for dental professionals, particularly dentists. Complementary and alternative medicine (CAM) can be helpful in managing and preventing these MSDs. The purpose of this study was to determine the prevalence of MSDs among dentists residing in east India and the use of CAM therapies for the management of MSDs among dentists. Dentists (N = 1082) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
(16 reference statements)
1
14
0
2
Order By: Relevance
“…Research into different CAM therapies being used by dental professionals revealed findings for the most common CAM approaches used by our participants was consistent with previous research 18,25,26 . However, the ranking among our participants varied from some of the literature with massage being first and yoga being third whereas in the literature massage and yoga have been the top two CAM approaches 18,25,26 .…”
Section: Discussionsupporting
confidence: 88%
“…Research into different CAM therapies being used by dental professionals revealed findings for the most common CAM approaches used by our participants was consistent with previous research 18,25,26 . However, the ranking among our participants varied from some of the literature with massage being first and yoga being third whereas in the literature massage and yoga have been the top two CAM approaches 18,25,26 .…”
Section: Discussionsupporting
confidence: 88%
“…Alexopoulos determinó una prevalencia del 62% en odontólogos griegos (13). Gupta et al describieron una prevalencia de 71% en odontólogos de la India (14). Tanto a nivel local como internacional, los odontólogos presentan elevados índices de dolor musculoesquelético.…”
Section: Discussionunclassified
“…In regard to the efficacy of plaque reduction, CHX was considered to be more effective. However, CHX rinsing can cause a number of local side effects[ 21 22 23 ] including extrinsic tooth and tongue brown staining, taste disturbance, enhanced supragingival calculus formation and less commonly, desquamation of the oral mucosa. Due to the side-effects of CHX users are not bale to accept CHX completely and for long-term use.…”
Section: Discussionmentioning
confidence: 99%